Synthesis of Hexamethylenetetramine Mono- and Di(P-Methoxyphenylacetochloride) - Ruzimurod Jurayev Sattorovich; Azimjon Choriev Uralivich; Bekzod Eshqulov Ravshan ugli (Engineering Proceedings)
In this study, hexamethylenetetramine mono- and di(p-methoxyphenylacetochloride) synthesis is presented in a clear and effective manner. Under mild conditions, p-methoxyphenylacetyl chloride and hexamethylenetetramine undergo a synthesis reaction. By adjusting the reactant and reaction conditions, the mono- and di-substituted products were produced selectively. The reaction of 4-methoxyphenylchloroacetate with various amines is a nucleophilic exchange reaction, and it was found that these reactions can proceed under normal conditions at the liquefaction temperature of the solvent. Before carrying out these reactions, the properties of amines were studied briefly. It can be found that the activity of the hydrogen attached to the nitrogen atom of amines depends on the nature of the group attached to the nitrogen. This relationship was expressed by Menshutkin’s kinetic equation and Arrinius’ equations. In addition, it became known that the reactions can be carried out easily due to the activity of the electrons that are not involved in the bond. To study the reactivity of tertiary amines, uratropin was chosen and its 4-methoxyphenylchloroacetate was reacted at 1:1 and 1:2 ratios, and the products were isolated. When the spectra of the obtained substances were analyzed, it was proven that a new substance was formed with the presence of an absorption region characteristic of the N-substituted amine group.